SAT0669 How do we use biologics in patients with a history of malignancy? an assessment of treatment patterns using scandinavian registers. (15th June 2017) - Chatzidionysiou, K; Aaltonen, K; Nordström, D; Gudbjornsson, B; Grondal, G; Geirsson, AJ; Steingrimsdottir, L; Frisell, T; Askling, J
Abstract : Background: Immune competence is of importance for the occurrence and outcome of malignancies. Robust data on risk of relapse of previous cancer following treatment with biological immune-modulators are scarce. Most treatment guidelines caution about their use in patients with a history of cancer, leaving rheumatologists with the decision whether a potential treatment benefit may offset any potential risk of cancer relapse. Objectives: To assess the overall use of biologics and the relative use of different biological drugs in RA patients with a history of cancer. Methods: As part of a Nordic collaboration, and using data from the ARTIS (Sweden), ROB-FIN (Finland), and ICEBIO (Iceland) biologics registers, we identified all patients with RA who initiated a first ever biological treatment 2010 through 2014. Through linkage to the national cancer registers, we identified those patients who had a history of any invasive malignancy (including squamous cell skin cancer) either within the five years preceding start of biological treatment ("recent history of malignancy") or more than five years before start of biological treatment ("non-recent history malignancy). Results: The age- and gender distributions were similar across countries and drugs. Initiators of non-TNFi biologics were older than TNFI-initiators; the median age at start was the highest for rituximab. Out of a total of 8065 bio-initiations, 6% occurred in individuals with a history of cancer (2% with a cancer within 5 years, and 4% with a cancer more than 5 years before treatment start. Whereas there was little variation (around 5%) across TNFi initiators, the proportion of patients with a history of cancer at treatment start was higher among rituximab initiators, in part explained by age (Table). There were only small variations across country (not shown). Conclusions: In Sweden, Finland and Iceland, one out of 20 biologics-initiators (and almost one out of five rituximab initiators) have a history of an invasive cancer, underscoring the need for more data on benefit/risks in this treatment context. The higher proportion in rituximab initiators is partly explained by differences in age at treatment start and reflects the preference for rituximab by clinicians for treatment of patients with history of cancer. Disclosure of Interest: K. Chatzidionysiou Consultant for: Roche, Pfizer, Abbvie, Elli-Lilly, UCB, K. Aaltonen: None declared, D. Nordström Speakers bureau: AbbVie, BMS, Lilly, MSD, Novartis, Pfizer, Roche, UCB, B. Gudbjornsson Speakers bureau: Actavis, Celgene, MSD, Pfizer, G. Grondal: None declared, A. Geirsson: None declared, L. Steingrimsdottir: None declared, T. Frisell: None declared, J. Askling Grant/research support from: AbbVie, Eli Lilly, Janssen, Merck, Pfizer, Roche, UCB, Samsung